Phase Diagram Modelling of a Multicomponent Aqueous Solution of Katwe Salt Lake, Uganda - Lwanyaga, J.D.; Kasedde, H.; Kirabira, J.B (International Conference on Environmental Science and Technology, 2019)
A methodology is developed to compute the phase diagram of a hexary system and to determine the mineral precipitation sequence upon removal of water. The methodology is applied to construct the phase diagram and precipitation sequence of the system ( in water. The thermodynamic model chosen is the Extended UNIQUAC. A 3D grid is constructed in order to solve this model in MATLAB. On the basis of this grid, a 3D phase diagram is calculated and a Jänecke projection is obtained. The precipitation sequence due to evaporation is calculated thus obtaining the coordinates of the solution along this path as well as the order of precipitation. The numerical model is also able to calculate all these steps for temperatures 0-110°C. In addition, the number of ions and the composition of the system can be varied in order to model other elective systems. The obtained results are well suited to be used for the design of sustainable salt extraction processes for both Sea and Lake brines.
Keywords: Evaporation; Extended UNIQUAC; Precipitation; Phase diagram; MATLAB